Nurses’ perceptions of professional dignity in hospital settings - Sabatino, Laura; Kangasniemi, Mari Katariina; Rocco, Gennaro; Alvaro, Rosaria; Stievano, Alessandro (2016)
Background:The concept of dignity can be divided into two main attributes: absolute dignity that calls for recognition of an inner worth of persons and social dignity that can be changeable and can be lost as a result of different social factors and moral behaviours. In this light, the nursing profession has a professional dignity that is to be continually constructed and re-constructed and involves both main attributes of dignity.Objectives:The purpose of this study was to determine how nurses described nursing’s professional dignity in internal medicine and surgery departments in hospital settings.Research design:The research design was qualitative.Ethical considerations:This study was approved by the ethics committees of the healthcare organizations involved. All the participants were provided with information about the purpose and the nature of the study.Participants:A total of 124 nurses participated in this study.Method:The data were collected using 20 focus group sessions in different parts of Italy. The data were analysed by means of a conventional inductive content analysis starting from the information retrieved in order to extract meaning units and sorting the arising phenomena into conceptually meaningful categories and themes.Results:Nursing’s professional dignity was deeply embedded in the innermost part of individuals. Regarding the social part of dignity, a great importance was put on the values that compose nursing’s professional identity, the socio-historical background and the evolution of nursing in the area considered. The social part of dignity was also linked to collaboration with physicians and with healthcare assistants who were thought to have a central role in easing work strain. Equally important, though, was the relationship with peers and senior nurses.Conclusion:The organizational environments under scrutiny with their low staffing levels, overload of work and hierarchical interactions did not promote respect for the dignity of nurses. To understand these professional values, it is pivotal to comprehend the role of different health professions in their cultural milieu and the evolution of the nursing profession in diverse countries.
Keywords: workplace elements; Nursing; inter/intra-professional relationships; Dignity of the human being; Absolute dignity